INVESTMENT FUNDS AND PRIVATIZATION PROCESS IN SERBIA - Simić, Nataša; Petrović, Vesna; Aničić, Dušan (Journal of process management and new technologies, 2019)
Both existence and efficient functioning of economic systems, which enable a greater, cheaper and quality production of material goods and services, rely, as a rule, on a relatively free market and private property as two inseparable assumptions of their efficient functioning. The construction of such systems can not end with ownership transformation and liberalization of internal and external economic flows. It is an important precondition for the functioning of such systems, but at the same time, just the beginning of their construction. The decisive role in raising efficient capital allocation at all levels has the construction of a sophisticated, open and competitive market which should be adjusted to the country's financial system. This implies the construction of a whole series of new financial institutions and fundamental reconstruction of the existing ones, the introduction of a large number of new financial instruments, especially in the form of securities, a thorough personnel reconstruction and innovation of educational institutions, but also the change of awareness of the broad social layers on the assumptions and modes of efficient operation. In that respect, investment funds play an important role.